An assessment of the ecological and conservation status of megafauna based on telemetry and census data : a case study of the African buffalo (Syncerus caffer) in post-civil war Mozambique - Chimimba, Christian Timothy (University of Pretoria, 2020)
Thesis (PhD)--University of Pretoria, 2019.